The Effect of Using the Teams Games Tournament (TGT) Strategy on Students’ Interest in Arabic Learning - Fuadah, Siti Sopwatul; Ghufron, Zaki; Ngaisah, Siti (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to investigate the effect of implementing the Teams Games Tournament strategy on students’ tendency to learn Arabic at MTs Negeri 2 Serang. The background of this study is the importance of increasing students’ tendency to learn Arabic, and the Teams Games Tournament strategy was chosen because it can increase motivation and student participation. The research method used is an experimental one-case study with a sample of one class consisting of 28 students. Data were collected through observation, questionnaires, interviews, and documents. The results showed that there was a positive effect of implementing the Teams Games Tournament strategy on students’ tendency to learn Arabic, with an average pre-test score of 62.43 and an average post-test score of 82.5. The results of the paired sample t-test and independent sample t-test showed that there was a significant effect of implementing the Teams Games Tournament strategy on students’ tendency to learn Arabic, with a sig value of 0.000 < 0.05. This study suggests that the Teams Games Tournament strategy can increase students’ tendency to learn Arabic and can be used as an alternative effective learning method. The results of this study can be used as a reference for Arabic teachers to increase students’ tendency to learn Arabic and can contribute to the development of more effective Arabic learning methods.